TECHNOLOGY OF FORMATION OF COGNITIVE INDEPENDENCE OF STUDENTS OF HIGHER PEDAGOGICAL EDUCATIONAL INSTITUTIONS IN THE PROCESS OF FOREIGN LANGUAGE LEARNING - Малихін, О. В. (Pedagogy of Higher and Secondary Education, 2011)
The article reveals some theoretical grounds for the technology of forming higher pedagogical educational establishments students' cognitive indeoendence in the process of foreign language learning. They resulted in the five steps of realizing the technology investigsted: organizing-and-preparing; dericting; modeling; reflecting; creating.